2012
DOI: 10.2175/106143012x13347678384729
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Near‐to‐Nature Stormwater Management on the Local Water Balance Using the Example of an Urban Development Area

Abstract: Near-to-nature stormwater management aims at replicating the quasi-natural local water balance and preserving the ecosystem's integrity of affected waters. Surface waters in the urban areas of Trier-Petrisberg are managed by a separate sewer system in conjunction with a complex retention system. To investigate the effect of this alternative rainwater management practice on the local water balance, a differentiated discharge and groundwater monitoring network with a high spatio-temporal measurement resolution h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In the same watershed, streamflow recessions were more gradual after urbanization with infiltration‐based SCMs compared to during urbanization. In another small watershed, groundwater levels were found not to significantly increase over time as urbanization with infiltration facilities took place, although stormflow became better controlled (Kessler et al, ). Although an infiltration‐based SCM in Annapolis, Maryland, United States, did intercept run‐off for small rainfall events, baseflow in the stream was significantly lower than in forested reference streams; there was no difference in baseflow between the watershed implemented with SCMs and an adjacent urban watershed with no SCM implementation (Fanelli et al, ).…”
Section: Results Of Existing Studiesmentioning
confidence: 99%
“…In the same watershed, streamflow recessions were more gradual after urbanization with infiltration‐based SCMs compared to during urbanization. In another small watershed, groundwater levels were found not to significantly increase over time as urbanization with infiltration facilities took place, although stormflow became better controlled (Kessler et al, ). Although an infiltration‐based SCM in Annapolis, Maryland, United States, did intercept run‐off for small rainfall events, baseflow in the stream was significantly lower than in forested reference streams; there was no difference in baseflow between the watershed implemented with SCMs and an adjacent urban watershed with no SCM implementation (Fanelli et al, ).…”
Section: Results Of Existing Studiesmentioning
confidence: 99%
“…Infiltration through stormwater facilities. Infiltrationfocused stormwater facilities may lead to more recharge from point sources instead of diffuse sources (Appleyard, 1995), which has been suggested to increase annual recharge (Ku et al, 1992;Göbel et al, 2004;Stephens et al, 2012;Barron et al, 2013;Hamel and Fletcher, 2014), although not in all cases (Keßler et al, 2012). Ideally with LID, the goal is for the urbanized water cycle to be equivalent to the pre-development cycle in overall fluxes (i.e.…”
Section: Introduction Of Directly Connected Impervious Surfacesmentioning
confidence: 99%
“…Studies have also investigated the effect of LID on groundwater recharge, where recharge is that part of infiltrated water not taken up by plants or evaporated but instead reaches the water table (Healy, ). These studies have revealed that (1) the effect of stormwater infiltration on recharge depends strongly on pre‐development recharge (Ku et al , ; Keßler et al , ; Stephens et al , ; Thomas and Vogel, ) and (2) groundwater mounding beneath stormwater facilities is more prevalent with low hydraulic conductivity, centralized spatial arrangement, or positioning at topographic lows (Endreny and Collins, ; Carleton, ; Machusick et al , ). Groundwater mounding may cause unintended damage to infrastructure, such as flooding of underground structures, groundwater leakage into wastewater pipes, vegetation damage, and pollutant mobilization (Göbel et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has used modelling to examine the potential effects of infiltrationbased stormwater facilities on groundwater levels beneath individual facilities (e.g., Machusick, Welker, & Traver, 2011;Newcomer, Gurdak, Sklar, & Nanus, 2014) and resulting from multiple facilities (Barron, Barr, & Donn, 2013;Carleton, 2010;Endreny & Collins, 2009;Göbel et al, 2004;Holman-Dodds, Bradley, & Potter, 2003;Ku, Hagelin, & Buxton, 1992;Locatelli et al, 2017;Maimone, O'Rourke, Knighton, & Thomas, 2011;Shuster, Gehring, & Gerken, 2007;Stephens, Miller, Moore, Umstot, & Salvato, 2012;Trinh & Chui, 2013). One monitoring analysis of groundwater elevations indicated that the effect of stormwater infiltration facilities is small but significant in Back Bay, Boston (Thomas & Vogel, 2012), although in another case, the effect of stormwater infiltration on groundwater elevations was not detectible (Keßler, Meyer, Seeling, Tressel, & Krein, 2012).…”
Section: Introductionmentioning
confidence: 99%